The Culture of the Babylonian Talmud. By Jeffrey Rubenstein. Pp. xiv + 232. Baltimore: Johns Hopkins University Press, 2003. isbn 0 8018 7388 6. £31 - Reif, Stefan C. (The journal of theological studies, 2005)
The author of this short but important monograph is a young scholar, with a growing reputation, who graduated at Columbia and the Jewish Theological Seminary in New York, specializes in the interpretation of talmudic stories, and teaches in the Skirball Department of Hebrew and Judaic Studies at New York University. Rubenstein follows David Weiss Halivni in presupposing the existence of a group of talmudic teachers who took the work of the Amoraim forward in a fairly radical way between the fifth and the seventh centuries.